2006
DOI: 10.1111/j.1471-0528.2006.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost of preterm birth: the low cost versus high value of tocolysis

Abstract: The consequences of preterm birth (PTB), to the individual and society at large, remain a major financial and personal burden. Babies born at the limits of viability, who survive, often have major neurological impairments, such as cerebral palsy, developmental delay and blindness. The cost of initial hospitalisation is more than $200 000 for each birth but takes no account of future costs once they leave the hospital. The major morbidities associated with extreme prematurity are respiratory distress syndrome (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…The tendency for earlier delivery is most evident in industrialized countries [1][2][3], partly resulting from advanced medical facilities which improve the survival rate of these preterm infants [4]. One of the consequences of preterm delivery is an increase in the proportion of preterm infants suffering from gastrointestinal complications, including necrotizing enterocolitis (NEC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency for earlier delivery is most evident in industrialized countries [1][2][3], partly resulting from advanced medical facilities which improve the survival rate of these preterm infants [4]. One of the consequences of preterm delivery is an increase in the proportion of preterm infants suffering from gastrointestinal complications, including necrotizing enterocolitis (NEC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth affects between 7 and 15% of all births in the United States, is a leading cause of perinatal morbidity and mortality, and poses significant financial burdens (1). Though morbidity is most concerning with early preterm births, studies have reported increased rates of neonatal medical problems and increased hospital costs both at delivery and for readmission in the first year of life for premature infants born between 35 and 37 weeks of age (late preterm birth) (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth accounts for approximately two-thirds of neonatal mortality. In particular, in underdeveloped and developing countries, it causes serious social and economic loses (4). Therefore, it is important to prevent or delay preterm births to improve the perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%